The Psychometric Properties of the Norwegian version of Schedule for Affective Disorders and Schizophrenia for School-Aged Children: Present and Lifetime Version (6-18) (Kiddie-SADS-PL) - Kornør, Hege; Skarphedinsson, Gudmundur (PsykTestBarn, 2016)
Description: Schedule for Affective Disorders and Schizophrenia for School-Age Children- Present and Lifetime Version (K-SADS-PL) is a semi-structured diagnostic interview used to evaluate current and lifetime episodes of psychopathology in children and adolescents. Joan Kaufman and colleagues revised the DSM-IV version. Anne Mari Sund and Marianne Aalberg Villabø translated the original material into Norwegian. Kaufman has also developed a DSM-5 version. She is the copyright holder of the international and the Norwegian version. The instrument can be used to evaluate at least 33 psychiatric disorders in children and adolescents. The mean administration time is 1½ hours. Individual administration to parents and the child may take 3 hours. The copyright holder does not require any formal competence for administration but generally, the administration is complex and a reliable and valid administration requires sufficient clinical experience and diagnostic competence. Literature search: Our systematic search resulted in 257 publications. We included fourteen publications on Norwegian data and four publications on Danish data. The Norwegian studies reported current prevalence of psychiatric disorders, inter-rater reliability or both. One study evaluated the convergent and divergent validity of the K-SADS-PL. Psychometrics: Inter-rater reliability showed in all cases an excellent agreement between two or more raters. In one study the K-SADS-PL showed that children with any anxiety disorder or ADHD had higher scores on dimensional anxiety/ADHD measures than children without any anxiety disorder or ADHD. Conclusion: Although the psychometric evidence for the Norwegian K-SADS-PL is limited, we conclude that qualified health personnel may use the instrument for clinical evaluation. The instrument closely resembles the DSM-IV diagnostic criteria. Excellent inter-rater reliability for central diagnostic groups does indeed support clinical usage. However, further psychometric studies are needed for the Norwegian version especially in terms of diagnostic accuracy and inter-rater reliability for specific diagnoses.